Probing the Scope and Mechanisms of Calcitriol Actions Using Genetically Modified Mouse Models - Dengshun Miao; David Goltzman (JBMR Plus, 2021)
ABSTRACT Genetically modified mice have provided novel insights into the mechanisms of activation and inactivation of vitamin D, and in the process have provided phenocopies of acquired human disease such as rickets and osteomalacia and inherited diseases such as pseudovitamin D deficiency rickets, hereditary vitamin D resistant rickets, and idiopathic infantile hypercalcemia. Both global and tissue‐specific deletion studies leading to decreases of the active form of vitamin D, calcitriol [1,25(OH)2D], and/or of the vitamin D receptor (VDR), have demonstrated the primary role of calcitriol and VDR in bone, cartilage and tooth development and in the regulation of mineral metabolism and of parathyroid hormone (PTH) and FGF23, which modulate calcium and phosphate fluxes. They have also, however, extended the spectrum of actions of calcitriol and the VDR to include, among others: modulation, jointly and independently, of skin metabolism; joint regulation of adipose tissue metabolism; cardiovascular function; and immune function. Genetic studies in older mice have also shed light on the molecular mechanisms underlying the important role of the calcitriol/VDR pathway in diseases of aging such as osteoporosis and cancer. In the course of these studies in diverse tissues, important upstream and downstream, often tissue‐selective, pathways have been illuminated, and intracrine, as well as endocrine actions have been described. Human studies to date have focused on acquired or genetic deficiencies of the prohormone vitamin D or the (generally inactive) precursor metabolite 25‐hyrodxyvitamin D, but have yet to probe the pleiotropic aspects of deficiency of the active form of vitamin D, calcitriol, in human disease. © 2020 American Society for Bone and Mineral Research © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.